Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12967-020-02235-w
|View full text |Cite
|
Sign up to set email alerts
|

Poor clinical outcome in metastatic melanoma is associated with a microRNA-modulated immunosuppressive tumor microenvironment

Abstract: Background: Interaction between malignant cells and immune cells that reside within the tumor microenvironment (TME) modulate different aspects of tumor development and progression. Recent works showed the importance of miRNA-containing extracellular vesicles in this crosstalk. Methods: Interested in understanding the interplay between melanoma and immune-related TME cells, we characterized the TCGA's metastatic melanoma samples according to their tumor microenvironment profiles, HLA-I neoepitopes, transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…These studies indicated that the IRGs in IRGPI played an important role in the occurrence and development of cancers, suggesting that our prognostic model would have good prospect and prognostic value in metastatic melanoma. The infiltration of immune cells in the tumor microenvironment played an important role in the progression of cancers, and it was also reported in metastatic melanoma in a wide variety studies 27,35 . Therefore, we calculated the score of 29 immune cells infiltration in each sample using ssGSEA to further explore the correlation between tumor microenvironment immune cells infiltration and IRGPI.…”
Section: Discussionmentioning
confidence: 79%
“…These studies indicated that the IRGs in IRGPI played an important role in the occurrence and development of cancers, suggesting that our prognostic model would have good prospect and prognostic value in metastatic melanoma. The infiltration of immune cells in the tumor microenvironment played an important role in the progression of cancers, and it was also reported in metastatic melanoma in a wide variety studies 27,35 . Therefore, we calculated the score of 29 immune cells infiltration in each sample using ssGSEA to further explore the correlation between tumor microenvironment immune cells infiltration and IRGPI.…”
Section: Discussionmentioning
confidence: 79%
“…This may reflect antitumor responses that are mediated by EVs or be a consequence of the release of tumor‐induced EVs by immune cells aiming to boost tumor progression. The latter is difficult to untangle due to the high complex network of gene regulation encompassed in the TME 5,23,26 . In breast tumors, M2 Mϕ‐derived exosomes sustain tumor cell dormancy 27 while glioma‐derived EVs inhibit T cell activation and PBMC migration 28 .…”
Section: Messages From Immune Cells To Melanoma Cellsmentioning
confidence: 99%
“…The latter is difficult to untangle due to the high complex network of gene regulation encompassed in the TME. 5,23,26 In breast tumors, M2 M -derived exosomes sustain tumor cell dormancy 27 30 Zhu and collaborators 31 analyzed the contents of NK-derived exosomes using NK-92 cells and identified higher levels of perforin and FasL in these vesicles than in the cell itself ( Fig. 1).…”
Section: Messages From Immune Cells To Melanoma Cellsmentioning
confidence: 99%
See 2 more Smart Citations